Sports and Games Union Policy - Kabale University (Kabale University, 2022)
Sports is an important activity, is the process of nation building, the role of sports in society can be summarized as follows. a) Building the physical anatomy of the body for both the young and the old b) Promoting teamwork and discipline given that many sports have strict rules and regulations c) Encouraging patriotism, closer social harmony and the world outlook. d) Fundamental life skills, sports is rich in values and virtues that help shape participating athletes into more productive self-worth and confident citizens. Such values as untiring work ethic-hard work endurance , perseverance , discipline ,leadership, how to follow , communication commitment time management , reliability, sportsmanship , responsibility , confidence character, creativity , socialization, motivation unselfishness/teamwork, self-awareness and alertness, how to handle adversity of losses and how to accept winning and losing graciously , among many other values are what sports help to instill into the participating athlete.